Esophageal perforations secondary to endoscopic procededures (report of three cases) - Ahmet TEZEL; Tülin ŞAHİN; Yasemin KOŞAR; Dilek OĞUZ; Kemal ARDA; Burhan ŞAHİN; Turhan CUMHUR (Turkish Journal of Gastroenterology, 2019)
-